Kontribusi Pemikiran Tgkh. Muhammad Zainuddin Abdul Madjid Nusa Tenggara Barat - Syafrianto, Syafrianto; Marhadi Efendi, Marhadi; SA, Saifullah; Julhadi, Julhadi; Asmaret, Desi (Institut Agama Islam Sumatera Barat Pariaman, 2025)
This research aims to examine the work and thoughts of Tuan Guru Kyai Haji Muhammad Zainuddin Abdul Madjid in the context of Islamic education and his contribution to the nation's moral development through Nahdlatul Wathan. The method used is qualitative research with a library research model, where data is collected through literature searches on the Dimensions platform and Google Scholar. To analyse the themes and linkages in the previous discussion, the author used the VOSviewer application. The results show that, firstly, Tuan Guru is a functional elite figure in Islamic society who not only acts as a cleric, but also as a spiritual and social guide. Secondly, Nahdlatul Wathan educational institutions have characteristics as general education institutions based on Islamic values, with a focus on forming a generation of faith and piety, as reflected in the slogan ‘The main thing is NW, the main thing is NW Iman and Taqwa.’ Third, Tuan Guru's thoughts and struggles in establishing Nahdlatul Wathan reflect a great effort to form national cadres with Islamic character and national spirit, as stated in his monumental work Hizb Nahdlatul Wathan. Thus, the contribution of Tuan Guru KH. Muhammad Zainuddin Abdul Madjid through Nahdlatul Wathan is not only important in the field of education and religion, but also plays a major role in the moral and spiritual development of the Indonesian nation.